Numerical Analysis in Enhancement of Heat Transfer with Pin Fins using Peripheral Protrusions - Muhammad Adnan (00000206332); Dr Majid Ali (USPCAS-E, NUST, Islamabad, 2021)
TH-259
Keywords: MS TEE Thesis MS Thesis